Cartel Dating - H. Peter Boswijk; Maurice J.G. Bun; Maarten Pieter Schinkel (Tinbergen Institute, 2016)
The begin and end dates of cartels are often ambiguous, despite competition authorities stating them with precision. The legally established infringement period(s), based on documentary evidence, need not coincide with the period(s) of actual cartel effects. In this paper, we show that misdating cartel effects leads to a (weak) overestimation of but-for prices and an underestimation of overcharges. Total overcharges based on comparing but-for prices to actual prices are a (weak) underestimation of the true amount overcharged, irrespective of the type and size of the misdating. The bias in antitrust damage estimation based on predicted cartel prices can have either sign. We extend the before-during-and-after method with an empirical cartel dating procedure that uses multiple structural break tests to determine the actual begin and end date(s) of the effects of collusive agreements. Empirical findings in the European Sodium Chlorate cartel corroborate our theoretical results.
Keywords: C22; C51; L41; 330; Cartel; antitrust damages; dates; structural change; break test; but-for